Salivary testosterone is related to self-selected training load in elite female athletes - Cook, C. J.; Beaven, C. M. (Physiology & Behavior, 2013)
Testosterone has been related to improved acute neuromuscular performance in athletic populations. It is our contention that testosterone may also contribute to improved volitional motivation and, when monitored longitudinally, may provide one proxy marker for readiness to perform.